Magnetic field surveys with a source of known magnetization. Issue 1 (1st December 2018) - Foss, Clive; Leslie, Keith; Pereira-Ishak, Najid
Abstract : A three component magnetometer developed to be drawn along a track beside drill core to log its magnetic susceptibility and remanent magnetization has been used to measure the external magnetic field of a palaeomagnetic sample over a survey area of side length 30 cm. The objective is to generate survey data from a source of known magnetization which can be used in testing magnetic field analysis algorithms (specifically those related to determination of source magnetization direction). The 3 component data directly emulates vector component survey data, is readily processed to derive gradient tensor data, and can be combined to generate TMI data. We have recovered measured magnetization directions to within 2° and 7° by inversion of TMI data from two initial test surveys.